A bibliometric analysis of scientific publications at Universiti Malaysia Sabah - Anath Rau Krishnan; Rizal Hamid; Geoffrey Harvey Tanakinjal; Saiful Bahri; Nalini Arumugam (PT Mattawang Mediatama Solution, 2025)
This study presents a comprehensive bibliometric analysis of scientific publications associated with Universiti Malaysia Sabah (UMS) from 1994 to 2024, tracing the university’s research progression over three decades. Using data extracted from the Scopus database, the study analyzes 9,217 publications by document type, open access (OA) status, and author keywords across three distinct decades using tools like Power Query, Microsoft Excel 365, and VOSviewer version 1.6.20. Findings reveal a steady increase in scientific publication productivity, with journal articles dominating output and OA publishing experiencing a significant surge in recent years. The keyword analysis highlights a consistent emphasis on local issues, particularly those related to Sabah and oil palm, while also reflecting the university’s growing engagement with emerging global themes such as COVID-19, machine learning, and deep learning. These insights suggest that future research efforts at UMS could be strategically aligned with other high-impact and trending areas, including climate change, renewable energy, public health, and artificial intelligence.This study offers the first comprehensive, cross-disciplinary bibliometric analysis of UMS publications, uniquely highlighting the university’s growing engagement with open access publishing. The findings offer valuable guidance for future policy decisions, particularly in enhancing publication funding, promoting balanced growth across disciplines, and advancing open science initiatives.